Analysis of the Effectiveness of Provision of Socio-Pedagogical Services to Young People in Khmelnytskyi Regional Center of Social Services for Family, Children and Young People - Yakubova, Liudmyla (Pedagogical Discourse, 2017)
This article describes and analyzes the provision of social and educational services staff of social services for family, children and youth. We have described the information relating to the activities of Khmelnytskyi Regional Centre of Social Services for Family, Children and Youth, which concerns the organization of social services for young people. We considered the possibility of accounting principles and the provision of social services, the order of social services category beneficiaries and glossary problems of which we have selected those that relate to young people, young families and others.. Analysis of the provision of social and educational services for youth based on the review and processing of scientific works of scientists and researchers. Therefore, we consider the highlight of their works features provide social and educational services to different categories of youth. Аctivity centers for social and psychological rehabilitation aims at enabling the greatest possible fulfillment of children and young people with limited functionality by bringing them into active life and the provision of appropriate social and educational services. Modern Ukrainian youth - the first generation of the process of socialization which takes place in terms of economic, social and value transformations; young people for the most part accepted this challenge, but then her life dramatically complicated the transition to adulthood, which previously consisted of the traditional attributes - free education, guaranteed job, economic stability - has become more uncertain. Accordingly, the way young people for adulthood and independence were different than twenty years ago. On the one hand, young people have an unprecedented number of choices in leisure activities, on the other – it faces new risks and challenges, offering educational sphere and the labor market. A range of modern opportunities and risks and is an important characteristic of the lives of young people, which ultimately leads to accelerated buildup quantification capabilities in some cases, or in the process of slowing down - in others. On the one hand, young people become stronger to adapt to constant change, and the other if adaptive capacity of young people is not high, it can lead to what is becoming one of the youth groups that need assistance and support. Taking into account the above mentioned activity takes a variety of social services and social services for the organization of youth who finds itself in crisis and in need of external support.